OPTIMALISASI PROSES REKRUTMEN KARYAWAN MELALUI ROBOTIC PROCESS AUTOMATION (RPA) DENGAN PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Rahayu, Sri; Marjani Santosa, Yaqutina (Politeknik Negeri Indramayu, 2024)
The manual recruitment process often requires significant time, effort, and cost, prompting companies to seek modern technologies that can recruit employees more effectively and efficiently. One of the technologies that has become increasingly popular today is RPA (Robotic Process Automation). This research proposes the use of RPA in conjunction with the SAW (Simple Additive Weighting) method as a solution to enhance efficiency in recruitment. By considering various criteria such as IPK, last education, skills, interview, salary, and documents, it is expected that companies can benefit from time and cost savings, improve candidate experience, and increase accuracy in the recruitment process. This research opts for a more effective and efficient approach by automating the employee recruitment process using RPA, enabling companies to accelerate the process, enhance objectivity, and achieve a 94% higher accuracy rate compared to the manual method.